Radiographic signs of gastrointestinal perforation in children: A pictorial review - Olugbenga T Awolaran (Wolters Kluwer Medknow Publications, 2015)
Plain abdominal radiographs remain an important aid for clinicians in the diagnosis of gastrointestinal perforation, especially in neonates and very sick children where clinical features of peritonitis may not be as prominent. Suggestive radiographic features are not always very obvious, especially when taken in the supine position and may lead to delayed or missed diagnosis. Through a pictorial review of plain radiographs, this article highlights a number of documented features of gastrointestinal perforation on X-ray in the paediatric setting, which increases the accuracy of diagnosis.